PENGARUH KESEMPATAN BERTUMBUH, RENCANA BONUS, BIAYA POLITIS, INSENTIF PAJAK, DAN PENSIUN CEO TERHADAP KONSERVATISME AKUNTANSI - Fadhlur Rahman Hamdi (2022)
This study is quantitative research and aims to analyze the significant effect of audit growth opportunities, bonus plans, political costs, tax incentives, and CEO retirement on accounting conservatism in banking sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Accounting conservatism as the dependent variable is proxied by the measurement model of Givoly and Hayn (2000). This study uses secondary data in the form of annual reports and company financial statements with a sample of 43 banking companies covering the period 2018 to 2020 was used for this study. The analysis method used is panel data regression with STATA version 14. The results of this study prove that (1) growth opportunities have no significant effect on accounting conservatism. (2) bonus plans have no significant effect on accounting conservatism. (3) political costs have no significant effect on accounting conservatism. (4) tax incentives have no significant effect on accounting conservatism. And (5) CEO retirement has no significant effect on accounting conservatism.